The Influence of English Teaching Model Reform and Psychological Intervention on Students’ Sports Habits - Yejun Li; Changfa Tang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Following graduation, a considerable proportion of individuals exhibit a linguistic proficiency akin to a state of linguistic inefficacy, hindering their competence in practical English Chinese translation and communication tasks. Consequently, the research aims to scrutinize the impact of English pedagogical model restructuring and psychological interventions on students' engagement in sporting activities. The primary focus of the study pertained to investigating the influence exerted by different English curriculum models in middle schools on the establishment of physical exercise routines among middle school students. Employing a multi-method approach encompassing literature review, surveys, expert consultations, and on-site visits, the research conducted a comprehensive examination across 12 randomly selected middle schools within a designated urban locale. Through a comparative analysis of historical and contemporary English curriculum frameworks, the study scrutinized various aspects, ranging from fostering students' keen interest in sports to cultivating enduring physical exercise habits and instilling the notion of lifelong wellness. Furthermore, the article delved into the diverse theoretical underpinnings and evolutionary trajectories characterizing the ongoing reform initiatives in physical education curricula in China, with particular emphasis on elucidating the implications of the latest curriculum standards. Substantial variances were observed in the levels of contentment among students with and without established exercise routines regarding their English classes, the instructional material, and the prescribed textbooks. While the majority of students exhibit a favourable disposition toward English classes overall, those lacking exercise habits evinced an 8.4% decline in satisfaction levels compared to their counterparts with exercise routines. Notably, satisfaction with English teaching content, particularly its alignment with physical exercise requirements, was notably lower among students devoid of exercise habits, with their satisfaction levels registering a nearly 10% decrease relative to their exercise-practicing peers. It is imperative to amalgamate the latest curriculum standards, dissect the components of the English curriculum, and endeavour to enhance the prevailing English curriculum framework to foster wholesome notions of physical education among students. Additionally, findings posit that integrating physical activities into English instruction and administering psychological interventions can significantly bolster students' proclivity towards sporting pursuits, thereby potentially enhancing their physical fitness and holistic welfare. These implications underscore the significance of amalgamating educational and psychological methodologies to promote a salubrious and dynamic lifestyle among students.